2009
DOI: 10.1007/s11010-009-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of −394C>G and −420C>G polymorphisms in the RETN gene with T2DM and CHD and a new potential SNP might be exist in exon 3 of RETN gene in Chinese

Abstract: Genetic variations of the human RETN gene are associated with metabolic phenotypes, including obesity, insulin sensitivity, diabetes, and coronary heart disease (CHD). There are few studies of two gene variants, -394C>G and -420C>G, in Chinese population. This study investigated the distribution of RETN gene, single nucleotide polymorphisms (SNPs), in Chinese Han population and the association of the polymorphisms with type 2 diabetes mellitus (T2DM) and CHD. In a population-based, case-control genetic associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…The lack of association between 44G/A, 62G/A, and 394C/G SNPs and obesity risk in our study was also reported in many studies (Cao and Hegele, 2001;Wang et al, 2002;Sentinelli et al, 2002;Chi et al, 2009;Hivert et al, 2009;Asano et al, 2010). Therefore, the effect of SNPs on obesity is quite variable.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The lack of association between 44G/A, 62G/A, and 394C/G SNPs and obesity risk in our study was also reported in many studies (Cao and Hegele, 2001;Wang et al, 2002;Sentinelli et al, 2002;Chi et al, 2009;Hivert et al, 2009;Asano et al, 2010). Therefore, the effect of SNPs on obesity is quite variable.…”
Section: Discussionsupporting
confidence: 56%
“…The genotypes for each resistin polymorphism 420C/G and 394C/G [promoter] and 44G/A and 62G/A [3¢-UTR] were determined by polymerase chain reaction (PCR)-restriction fragment length polymorphism as described by Cao and Hegele (2001), Duman et al (2007), Tang et al (2008), and Chi et al (2009). PCR products and the digest product were resolved by 2% agarose gel electrophoresis and visualized by ethidium bromide staining.…”
Section: Dna Analysismentioning
confidence: 99%
“…In our population, however, there were no differences in either genotype distribution or allelic frequencies for both polymorphisms examined between the Control group and the obesity or the T2D groups; therefore, no associations were found in any of the genetic models. These results were in accordance with previous reports for Asians, Northern Americans, and Europe [21,23,24,36,37,[39][40][41][42][43]45,46]. However, two studies, conducted in Asians [8] and Africans [9] population have shown an increased risk of developing T2D related to the g.-420C>G mutation.…”
Section: T2d Is a Leading Cause Of Morbidity And Mortality Among Adultssupporting
confidence: 92%
“…Five studies were not written in English or Spanish, six lacked sufficient information, seven were not case-control studies, two were duplicate studies, three considered different BMI cutoffs for obesity, and one focused on children and were therefore excluded (Figure 1). From the remaining twenty-eight studies, eighteen focused on the g.-420C>G polymorphism [8,9,19,21,[23][24][25][26][35][36][37][38][39][40][41][42][43][44] and four on the c.+62A>G polymorphism [22,25,45,46]. Our current study was also considered for the meta-analysis.…”
Section: Characteristics Of the Studies From Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation